Maternal clinical findings in malaria in pregnancy in a region of northwestern Colombia (2013)
ABSTRACT: In malaria-endemic regions of Latin America, little is known about malaria in pregnancy. To characterize the clinical and laboratory findings of maternal infection, we evaluated 166 cases of pregnant women infected with Plasmodium spp. in a prospective study conducted in northwestern Colombia during 2005–2006. A total of 89.8% (149 of 166) had fever or a history of fever in the past 48 hours, 9.0% (15 of 166) had severe malaria, of which 66.7% was caused by Plasmodium vivax and 33.3% by P. falciparum. Hepatic dysfunction was the main complication (9 of 15) observed. The proportion of severe cases was similar for both species (P = 0.41). In malaria-endemic areas of Colombia, malaria in pregnancy has a broad clinical spectrum. In pregnant women, P. vivax infection frequently leads to organ-specific complications.